2020
DOI: 10.1101/2020.06.30.180224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ribosome modulates folding inside the ribosomal exit tunnel

Abstract: Proteins commonly fold cotranslationally on the ribosome, while the nascent chain emerges from the ribosomal tunnel. Protein domains that are sufficiently small can even fold while still located inside the tunnel. However, the effect of the tunnel on the folding dynamics of these domains is still not well understood. Here, we combine optical tweezers with single-molecule FRET and molecular dynamics simulations to investigate folding of the small zinc-finger domain ADR1a inside and at the vestibule of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…These results are consistent with ribosome exit tunnel studies that, using optical tweezers and molecular dynamics simulations, showed excluded volume effects and electrostatic interactions contribute to substrate folding (28).…”
Section: Molecular Interactions Of Translocation Complexsupporting
confidence: 92%
“…These results are consistent with ribosome exit tunnel studies that, using optical tweezers and molecular dynamics simulations, showed excluded volume effects and electrostatic interactions contribute to substrate folding (28).…”
Section: Molecular Interactions Of Translocation Complexsupporting
confidence: 92%
“…Optical tweezers are widely used in vitro to investigate protein folding (10), and also to quantify material properties of isolated cells (11). In its simplest form, an optical trap is formed by tightly focusing a laser beam, whereby objects with a refractive index higher than the surroundings are drawn along the intensity gradient towards the focus of the beam by a harmonic force (12).…”
Section: Introductionmentioning
confidence: 99%